The Influence of Green Banking Practices on Customer Satisfaction: The Role of Privacy - Fauzan, Alfian Kurnia; Safuan, Safuan; Syah, Tantri Yanuar Rahmat; Edastama, Primasatria (Yayasan Riset dan Pengembangan Intelektual, 2026)
Green banking has become a strategic imperative for financial institutions worldwide, but emerging markets face a unique challenge: balancing sustainability commitments with customer trust in data security. This study examines how privacy protection strengthens the relationship between green banking practices and customer satisfaction in Indonesia's digital banking sector. Using structural equation modeling with 313 users of green banking services in state-owned banks, the study found that privacy acts as a critical mediating factor, amplifying customer satisfaction, which in turn drives customer trust, loyalty, and continued adoption of green financial services. The implications go beyond regulatory compliance to reveal how banks can differentiate themselves competitively through integrated sustainability and privacy governance. This